2012
DOI: 10.1002/jrs.4214
|View full text |Cite
|
Sign up to set email alerts
|

Insitu Raman spectroscopic observation of sequential hydrolysis of stannous chloride to abhurite, hydroromarchite, and romarchite

Abstract: The sensitive character of tin oxidation and the effect of pH on the solubility of tin species highlight several challenges for further understanding tin speciation within aqueous solutions. Raman spectroscopic monitoring of aqueous stannous chloride solutions over a broad pH range resulted in the observation of several insoluble tin species (e.g. abhurite and hydroromarchite) suspended within the neutral and alkaline solutions. An aqueous tin speciation mechanism was proposed based on semi‐quantitative indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…4). The Raman spectra are in a good agreement with literature data [25], including the sequential hydrolysis of a tin(II) chloride solution and reference data from abhurite, Sn II 21 O 6 Cl 16 (OH) 14 , and hydroromarchite, Sn II 3 O 2 (OH) 2 [15], as well as both minerals [10]. In the case of abhurite, a characteristic strong Raman signal at 206 cm −1 was observed next to a medium band at 256 cm −1 .…”
Section: Raman Spectra Of Sn II 3 O 2 (Oh) 2−x Cl X and Certain Tin(isupporting
confidence: 78%
See 1 more Smart Citation
“…4). The Raman spectra are in a good agreement with literature data [25], including the sequential hydrolysis of a tin(II) chloride solution and reference data from abhurite, Sn II 21 O 6 Cl 16 (OH) 14 , and hydroromarchite, Sn II 3 O 2 (OH) 2 [15], as well as both minerals [10]. In the case of abhurite, a characteristic strong Raman signal at 206 cm −1 was observed next to a medium band at 256 cm −1 .…”
Section: Raman Spectra Of Sn II 3 O 2 (Oh) 2−x Cl X and Certain Tin(isupporting
confidence: 78%
“…The stability range of abhurite and its transition to hydroromarchite depending on the pH value has been discussed [13]. Edwars et al [8] 2013, Chen and Grandbois [15] reported in situ Raman spectroscopic investigations of the sequential hydrolysis of tin(II) chloride to abhurite, hydroromarchite and finally to romarchite, Sn II O. Their research demonstrates the formation of abhurite from a tin(II) chloride solution by adding a sodium hydroxide solution.…”
Section: Introductionmentioning
confidence: 97%
“…The methods employed in this study demonstrate the usefulness of Raman spectroscopy for the characterization of complex heterogeneous mixtures. [228] Gruber and coworkers present Raman scattering results for crystalline Li x Si y compounds. The expermental results were compared with theoretical data obtained from DFT calculations.…”
Section: Single Crystalsmentioning
confidence: 99%
“…Chen and coworkers carried out in situ Raman spectroscopic observation of sequential hydrolysis of stannous chloride to abhurite, hydroromarchite, and romarchite. The methods employed in this study demonstrate the usefulness of Raman spectroscopy for the characterization of complex heterogeneous mixtures . Gruber and coworkers present Raman scattering results for crystalline Li x Si y compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Currently selected conventional offline amino acid analysis methods that use high‐performance liquid chromatography (HPLC) or an amino acid analyser are not suitable for process monitoring, mainly due to long intervals between sampling and obtaining analytical results caused by time‐consuming procedures. In recent years, in a variety of fields, the hydrolysis process has been studied and monitored by different spectroscopic sensors, including near‐infrared (NIR) spectroscopy, infrared (IR) spectroscopy, Raman spectroscopy, ultraviolet–visible (UV–Vis) spectroscopy, nuclear magnetic resonance (NMR) spectroscopy and other spectroscopic sensors . In the TCM pharmaceutical industry, NIR spectroscopy‐based methods were developed by Wu et al .…”
Section: Introductionmentioning
confidence: 99%